Características sedimentológicas de reservatórios siliciclásticos e carbonáticos - MEIGUINS, Humberto de Alencar Costa (2019)
The study of the porosity and permeability of hydrocarbon reservoirs is part of what is called petrophysical characterization of reservoirs. So, the characterization of reservoirs, through the determination of rock properties, is extremely relevant for petroleum geology, as petroleum engineering. and geophysics, in search of new oil and gas deposits. Such tools provide param-eters for assessing the economical potential of an oilfield. In this context, it is very important to know the sedimentological characteristics of hydrocarbon reservoirs and their influence on porosity and permeability. Although there are different types of reservoir rocks, most reserves are found in sandstone and carbonate rocks, as they have adequate porosity and permeability for oil accumulation. While sandstones are relatively homogeneous, carbonate rocks can pre-sent significant variations in pore size and pore distribution, making it difficult, for example, to simulate pore fluid transport processes. Brazil has important liquid and / or gaseous hydro-carbon deposits in conventional and unconventional reservoirs, which, when economically explored, may represent important changes in the country's oil and gas industry.